The effects of gender stereotyping in the workplace (gender stereotyping productive or destructive?) - de la torre, Lovely; Gargueña, Diane Mae.; Labanon, Lisha Marie; Mayangao, Ian Jermie; Niego, Alma Kristine; Paredes, Sheila Dawn.; Pobre, Marie Justine (2010)
The study was performed to determine the effect/s of gender stereotyping in the workplace. Gender stereotyping in the workplace was measured through various business processes such as recruitment, hiring, positioning, and promotions. The researchers conducted key informant interviews and focus group discussions to the managers and non-managers of chosen business organizations situated in Iloilo City and Bacolod City. Through these methodologies, the researchers found out that gender stereotyping increases productivity in the workplace. This suggests that gender stereotyping does not always lead to gender discrimination.
Research Paper (Mgt 199 - Management Research). -- Iloilo City : UPV-CM, October 13, 2010.